3D-rGO-Fe3O4-CS-SA composite modified electrode and its preparation method and application

The electrodes modified by 3D-rGO-Fe3O4-CS-SA complex solves the problem of poor enantiomer recognition effect in the prior art, and achieves a more efficient chiral recognition effect.

CN116087288BActive Publication Date: 2025-04-08CHANGZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211334768.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-28
Publication Date
2025-04-08
Estimated Expiration
2042-10-28

AI Technical Summary

Technical Problem

In the existing electrochemical chiral recognition technology, the peak current ratio of the enantiomer is relatively low, making it difficult to achieve efficient recognition.

Method used

The electrode was modified by 3D-rGO-Fe3O4-CS-SA complex, and the electrode was modified by three-dimensional reduction of graphene oxide, iron tetraoxide, chitosan and sodium alginate complexes to improve the adsorption and recognition ability of the enantiomers.

Benefits of technology

The recognition ability of enantiomers is significantly improved, and the peak current ratio reaches 2.05, which is better than the prior art.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116087288B_ABST
    Figure CN116087288B_ABST
Patent Text Reader

Abstract

The invention belongs to the field of analytical chemistry, and particularly relates to a 3D-rGO-Fe3O4-CS-SA composite modified electrode and a preparation method and application thereof, wherein the preparation comprises the following steps: preparing a three-dimensional reduced graphite oxide, ferroferric oxide, chitosan and sodium alginate (3D-rGO-Fe3O4-CS-SA) composite solution; preparing a 3D-rGO-Fe3O4-CS-SA modified electrode; and electrochemically identifying 2-amino-1-(4-nitrophenyl)-1,3-propanediol enantiomers. The invention has the following beneficial effects: the preparation method of the 3D-rGO-Fe3O4-CS-SA modified electrode is simple, the stability is high, and the chiral recognition effect is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of analytical chemistry, and particularly relates to a 3D-rGO-Fe3O4-CS-SA composite modified electrode and a preparation method and application thereof. Background Art

[0002] Chirality is an essential property of nature. Most organic molecules have a pair of mirror images, existing as (+)-enantiomers or (-)-enantiomers. Usually, these two isomers have different physical and chemical properties. At present, the commonly used chiral recognition techniques mainly include chromatography, spectroscopy, mass spectrometry and sensor methods. Chiral isomers are widely present in drugs, pesticides, food additives, humans and the environment. The development of simple, fast and accurate recognition has become a hot spot and frontier direction in analytical chemistry in recent years, which has important research significance. Electrochemical methods have attracted widespread attention due to their advantages such as simple operation and fast detection.

[0003] However, the peak current ratio of enantiomers in electrochemical chiral recognition in the prior art is relatively low. For example, Li et al. used hydroxypropyl chitosan (HPCS) covalently bound to multi-walled carbon nanotubes to recognize mandelic acid enantiomers, and the recognition effect was I R / I S =1.48. Zou et al. used soluble starch (SS) and chitosan (CS) as materials to prepare chiral electrodes for the recognition of tyrosine, and the recognition effect was I R / I S =1.38. Summary of the invention

[0004] In order to provide a modified electrode with obvious electrochemical chiral recognition effect, the present invention provides a 3D-rGO-Fe3O4-CS-SA complex modified electrode using electrochemical chiral recognition and its preparation method and application, including an electrode and a 3D-rGO-Fe3O4-CS-SA complex modified on the surface of the electrode, which is obtained by dripping a 3D-rGO-Fe3O4-CS-SA suspension on the surface of the electrode and then drying it. The three-dimensional reduced graphene oxide has a large specific surface area and can significantly improve the conductivity. Ferroferric oxide has good magnetism. Chitosan and sodium alginate can form a new multi-void network structure that is beneficial to the adsorption of enantiomers. The preparation process is simple, the stability is high, and the recognition ability of enantiomers is significantly improved.

[0005] The preparation method of 3D-rGO-Fe3O4-CS-SA composite modified electrode for electrochemical chiral recognition comprises the following steps:

[0006] (1) Preparation of 3D-rGO-Fe3O4 powder: Weigh a designed amount of GO and disperse it in deionized water by sonication; add L-cysteine ​​and FeCl3·6H2O to the above solution in sequence, then quickly drop ammonia water, heat the mixture in an oil bath, cool it to room temperature, repeat hysteresis separation, wash the black product with deionized water, and freeze-dry to obtain 3D-rGO-Fe3O4 powder;

[0007] (2) Preparation of 3D-rGO-Fe3O4-CS-SA suspension: A designed amount of 3D-rGO-Fe3O4 powder was weighed to prepare a dispersion, and the carboxylic acid groups in 3D-rGO-Fe3O4 were activated with EDC·HCl and NHS, and then dispersed in a mixed solution of CS and SA with a mass ratio of 1:1, and ultrasonicated to obtain a 3D-rGO-Fe3O4-CS-SA suspension.

[0008] (3) Preparation of 3D-rGO-Fe3O4-CS-SA modified electrode: Take an appropriate amount of 3D-rGO-Fe3O4-CS-SA suspension and drop it on the electrode surface. Dry it under an infrared lamp to obtain a 3D-rGO-Fe3O4-CS-SA modified electrode.

[0009] Furthermore, the mass concentration ratio of EDC·HCl to NHS was 1.2:1.

[0010] Furthermore, the ratio of the total mass of CS and SA to the mass of 3D-rGO-Fe3O4 powder is 5:4.

[0011] Furthermore, the method for preparing the mixed solution of CS and SA includes: dissolving CS in a 1% dilute acetic acid solution to prepare a CS solution; dissolving SA in deionized water to prepare a SA solution, and then uniformly mixing the CS solution and the BSA solution, ultrasonicating, and stirring.

[0012] Furthermore, the concentration of CS and SA in the composite solution was 1 mg / ml.

[0013] More specifically, 25 mg of CS was weighed and placed in a 25 ml volumetric flask, and 1% dilute acetic acid solution was added to dissolve and dilute to the scale; 25 mg of SA was weighed and placed in a 25 ml volumetric flask, and deionized water was added to dissolve and dilute to the scale; then the two were mixed, ultrasonicated for 1 hour, and stirred at 60° C. for 24 hours to obtain a CS-SA solution.

[0014] The drop coating volume of 3D-rGO-Fe3O4-CS-SA suspension was 8 μL.

[0015] The present invention also provides an application of a 3D-rGO-Fe3O4-CS-SA complex modified electrode that can be used for electrochemical chiral recognition, which is used for chiral recognition of 2-amino-1-(4-nitrophenyl)-1,3-propanediol enantiomers, comprising the following steps: weighing a certain amount of R- / S-2-amino-1-(4-nitrophenyl)-1,3-propanediol and placing it in a volumetric flask, adding a certain amount of prepared phosphate buffer solution PBS, shaking to obtain an enantiomer solution, immersing the 3D-rGO-Fe3O4-CS-SA complex modified electrode in the enantiomer solution, taking it out, and drying it under an infrared lamp, thereby obtaining a prepared 2-amino-1-(4-nitrophenyl)-1,3-propanediol enantiomer electrode;

[0016] A three-electrode system was adopted, with 2-amino-1-(4-nitrophenyl)-1,3-propanediol enantiomer electrode as the working electrode, platinum electrode as the counter electrode, and saturated calomel electrode as the reference electrode. The three-electrode system was immersed in the prepared 0.1M K3Fe(CN)6 solution at room temperature for differential pulse testing with a potential range of -0.2 to 0.6V.

[0017] Furthermore, the concentrations of the prepared (R)-2-amino-1-(4-nitrophenyl)-1,3-propanediol and (S)-2-amino-1-(4-nitrophenyl)-1,3-propanediol solutions were both 5 mM, the pH of the PBS solution was 7, the concentration was 0.1 M, and the standing time was 15 min.

[0018] Reduced graphene oxide (3D-rGO) has a unique network porous structure that gives it an ultra-high specific surface area and conductivity. As an emerging sensing material, it has been used to construct electrochemical sensors. Ferroferric oxide (Fe3O4) nanoparticles have good magnetic properties, excellent surface activity and biocompatibility. Fe3O4 nanoparticles are uniformly loaded on the rGO surface through covalent action, making its rigid structure more stable. At the same time, there are many adsorption sites on Fe3O4, which is conducive to the binding of chiral selectors. Chitosan (CS), as a natural polysaccharide, has excellent optical activity and a large number of chiral sites. It has excellent hydrophilicity and good adhesion and is widely used in the construction of electrochemical chiral sensors. Sodium alginate (SA) is a linear polysaccharide copolymer derived from brown algae. It contains a large number of chiral sites. It can be combined with chitosan through electrostatic adsorption to form a new porous network structure, which is conducive to the adsorption of enantiomers. Therefore, we constructed an electrochemical chiral surface by covalently bonding chitosan and sodium alginate with ferroferric oxide on reduced graphene oxide through electrostatic adsorption, further improving its stability and recognizing the enantiomers of 2-amino-1-(4-nitrophenyl)-1,3-propanediol with a recognition effect of I R / I S=2.05. Compared with the prior art, the beneficial effects of the present invention are: the preparation operation process of the 3D-rGO-Fe3O4-CS-SA modified electrode is simple, the stability is high, and the modified electrode has an obvious recognition effect on the enantiomer. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is the scanning electron microscope image of 3D-rGO-Fe3O4 in Example 1.

[0020] Figure 2 This is a scanning electron microscope image of the 3D-rGO-Fe3O4-CS-SA composite in Example 1.

[0021] Figure 3 This is the differential pulse voltammogram of the 3D-rGO-Fe3O4, CS and SA composite modified electrodes used for chiral recognition of 2-amino-1-(4-nitrophenyl)-1,3-propanediol enantiomers in Example 1.

[0022] Figure 4 This is the cyclic voltammetry scan diagram used for studying the stability of 3D-rGO-Fe3O4, CS and SA composites in Example 2.

[0023] Figure 5 3D-rGO-Fe3O in Example 3 4- The relationship between CV and SA content in CS-SA modified electrode and peak current value I R / I S impact.

[0024] Figure 6 The 3D-rGO-Fe3O 4- Effect of 3D-rGO content in CS-SA modified electrode on peak current value I R / I S impact.

[0025] Figure 7 The figure is the differential pulse voltammogram of the CS and SA complex modified for chiral recognition of 2-amino-1-(4-nitrophenyl)-1,3-propanediol enantiomers in the comparative example.

[0026] Figure 8 This is the cyclic voltammetry scan of the CS-SA modified electrode in the comparative example. DETAILED DESCRIPTION

[0027] The present invention will now be further described in conjunction with specific embodiments. The following embodiments are intended to illustrate the present invention rather than to further limit the present invention.

[0028] The present invention uses a three-dimensional reduced graphene oxide, ferroferric oxide, chitosan and sodium alginate composite modified electrode to identify the enantiomers of 2-amino-1-(4-nitrophenyl)-1,3-propanediol according to the following method:

[0029] R R / S =I R / I S

[0030] △E=E R -E S

[0031] In the formula, R R / S represents the oxidation peak current ratio of 2-amino-1-(4-nitrophenyl)-1,3-propanediol enantiomers, △E represents the oxidation peak potential difference of 2-amino-1-(4-nitrophenyl)-1,3-propanediol enantiomers, I R and I S represents the oxidation peak current of R-2-amino-1-(4-nitrophenyl)-1,3-propanediol and S-2-amino-1-(4-nitrophenyl)-1,3-propanediol, E R and E S They represent the oxidation peak potentials of R-2-amino-1-(4-nitrophenyl)-1,3-propanediol and S-2-amino-1-(4-nitrophenyl)-1,3-propanediol, respectively.

[0032] In the following examples, the drop coating amount of 3D-rGO-Fe3O4-CS-SA on the electrode surface is 0.0226 mg / cm 2 .

[0033] Example 1

[0034] (1) Preparation of 3D-rGO-Fe3O4 powder: 100 mg of GO was weighed and dispersed in 100 mL of deionized water and ultrasonicated; 200 mg of L-cysteine ​​and 200 mg of FeCl3·6H2O were added to the above solution in sequence, and then 1.5 ml of ammonia water was quickly added dropwise. The mixture was placed in an oil bath and heated at 85°C for 3 h. After cooling to room temperature, it was repeatedly subjected to hysteresis separation, washed with deionized water, and freeze-dried.

[0035] (2) Preparation of CS-SA mixed solution: weigh 25 mg of CS and place it in a 25 ml volumetric flask, add 1% dilute acetic acid solution to dissolve and dilute to the scale; weigh 25 mg of SA and place it in a 25 ml volumetric flask, add deionized water to dissolve and dilute to the scale; mix CS and SA in a ratio of 1:1, ultrasonicate for 1 h, and stir at 60°C for 24 h to prepare a CS-SA mixed solution.

[0036] (3) Preparation of 3D-rGO-Fe3O4-CS-SA composite suspension: Weigh 4 mg of the 3D-rGO-Fe3O4 powder prepared in step (1) and disperse it in a small amount of deionized water, add 6 mg of EDC·HCl and 5 mg of NHS to activate the carboxylic acid group, add it to 5 mL of the CS-SA solution prepared in step (2), and ultrasonicate to obtain a 3D-rGO-Fe3O4-CS-SA suspension. Preferably, the ratio of the total mass of CS and SA to the mass of 3D-rGO-Fe3O4 powder is 5:4.

[0037] (4) Preparation of 3D-rGO-Fe3O4-CS-SA modified electrode: Take 8 μL of the suspension prepared in step (3) and drop it on the electrode surface, and dry it under an infrared lamp to obtain a 3D-rGO-Fe3O4-CS-SA modified electrode.

[0038] (5) Preparation of 2-amino-1-(4-nitrophenyl)-1,3-propanediol enantiomer electrode: Weigh 53 mg of R- / S-2-amino-1-(4-nitrophenyl)-1,3-propanediol into a 50 ml volumetric flask, add phosphate buffer (PBS, pH = 7) to dissolve to the mark, shake well, soak the 3D-rGO-Fe3O4-CS-SA modified electrode prepared in step (4) in the enantiomer solution for 15 min, take out, and dry under an infrared lamp. The 2-amino-1-(4-nitrophenyl)-1,3-propanediol enantiomer electrode is thus prepared.

[0039] (6) Electrochemical identification of 2-amino-1-(4-nitrophenyl)-1,3-propanediol enantiomers: A three-electrode system was used, with the 2-amino-1-(4-nitrophenyl)-1,3-propanediol enantiomer electrode as the working electrode, the platinum electrode as the counter electrode, and the saturated calomel electrode as the reference electrode. The three-electrode system was immersed in a prepared 0.1M K3Fe(CN)6 solution at room temperature and a differential pulse test was performed. The potential range was -0.2 to 0.6 V, see Figure 3 .

[0040] (7) Based on Example 1, the other conditions remained unchanged, and the amounts of CS and SA were modified. The specific amount added was 5 ml and the concentration of the CS-SA mixed solution was 2 mg / ml. Results I R / I S The ratio was 1.46; the dosage of CS and SA was modified, the specific amount added was 5 ml and the concentration of CS-SA mixed solution was 5 mg / ml, the result I R / I S The ratio is 1.35, which is lower than the recognition effect of Example 1 when the addition amount is 5 ml and the mass concentration is 1 mg / ml.

[0041] Example 2

[0042] (1) Preparation of 3D-rGO-Fe3O4 powder: 100 mg of GO was weighed and dispersed in 100 mL of deionized water and ultrasonicated; 200 mg of L-cysteine ​​and 200 mg of FeCl3·6H2O were added to the above solution in sequence, and then 1.5 ml of ammonia water was quickly added dropwise. The mixture was placed in an oil bath and heated at 85°C for 3 h. After cooling to room temperature, it was repeatedly subjected to hysteresis separation, washed with deionized water, and freeze-dried.

[0043] (2) Preparation of CS-SA mixed solution: weigh 25 mg of CS and place it in a 25 ml volumetric flask, add 1% dilute acetic acid solution to dissolve and dilute to the scale; weigh 25 mg of SA and place it in a 25 ml volumetric flask, add deionized water to dissolve and dilute to the scale; mix CS and SA in a ratio of 1:1, ultrasonicate for 1 h, and stir at 60°C for 24 h to prepare a CS-SA mixed solution.

[0044] (3) Preparation of 3D-rGO-Fe3O4-CS-SA composite suspension: 4 mg of the 3D-rGO-Fe3O4 powder prepared in step (1) was weighed and dispersed in a small amount of deionized water. After adding 6 mg of EDC·HCl and 5 mg of NHS to activate the carboxylic acid group, the mixture was added to 5 mL of the CS-SA solution prepared in step (2) and ultrasonicated to obtain a 3D-rGO-Fe3O4-CS-SA suspension.

[0045] (4) Preparation of 3D-rGO-Fe3O4-CS-SA modified electrode: Take 8 μL of the suspension prepared in step (3) and drop it on the electrode surface, and dry it under an infrared lamp to obtain a 3D-rGO-Fe3O4-CS-SA modified electrode.

[0046] (5) Electrochemical stability study: A three-electrode system was used, with 3D-rGO-Fe3O4-CS-SA electrode as the working electrode, platinum electrode as the counter electrode, and saturated calomel electrode as the reference electrode. The three-electrode system was immersed in a prepared 0.1M K3Fe(CN)6 solution at room temperature and cyclic voltammetry was performed. The scanning potential range was -0.2 to 0.6 V, and the scanning rate was 100 mV·s -1 , cycle scan 100 times, see Figure 4 .

[0047] Example 3

[0048] (1) Preparation of 3D-rGO-Fe3O4 powder: 100 mg of GO was weighed and dispersed in 100 mL of deionized water and ultrasonicated; 200 mg of L-cysteine ​​and 200 mg of FeCl3·6H2O were added to the above solution in sequence, and then 1.5 ml of ammonia water was quickly added dropwise. The mixture was placed in an oil bath and heated at 85°C for 3 h. After cooling to room temperature, it was repeatedly subjected to hysteresis separation, washed with deionized water, and freeze-dried.

[0049] (2) Preparation of CS-SA mixed solution: weigh 50 mg of CS and place it in a 50-ml volumetric flask, add 1% dilute acetic acid solution to dissolve and dilute to the scale; weigh 50 mg of SA and place it in a 50-ml volumetric flask, add deionized water to dissolve and dilute to the scale, mix according to the CS:SA concentration ratio of 3:1, 2:1, 1:1, 1:2, and 1:3, ultrasonicate for 1 h, and stir at 60°C for 24 h to prepare mixed solutions of various ratios and concentrations.

[0050] (3) Preparation of 3D-rGO-Fe3O4-CS-SA composite suspension: 4 mg of the 3D-rGO-Fe3O4 powder prepared in step (1) was weighed and dispersed in a small amount of deionized water. After adding 6 mg of EDC·HCl and 5 mg of NHS to activate the carboxylic acid group, the mixture was added to 5 mL of the CS-SA solution prepared in step (2) and ultrasonicated to obtain a 3D-rGO-Fe3O4-CS-SA suspension.

[0051] (4) Preparation of 3D-rGO-Fe3O4-CS-SA modified electrode: Take 8 μL of the suspension prepared in step (3) and drop it on the electrode surface, and dry it under an infrared lamp to obtain a 3D-rGO-Fe3O4-CS-SA modified electrode.

[0052] (5) Preparation of 2-amino-1-(4-nitrophenyl)-1,3-propanediol enantiomer electrode: Weigh 53 mg of R- / S-2-amino-1-(4-nitrophenyl)-1,3-propanediol into a 50 ml volumetric flask, add phosphate buffer (PBS, pH = 7) to dissolve to the mark, shake well, soak the 3D-rGO-Fe3O4-CS-SA modified electrode prepared in step (3) in the enantiomer solution for 15 min, take it out, and dry it under an infrared lamp. The 2-amino-1-(4-nitrophenyl)-1,3-propanediol enantiomer electrode is thus prepared.

[0053] (6) Electrochemical characterization of the loading of chiral instant noodle materials: A three-electrode system was used, with 2-amino-1-(4-nitrophenyl)-1,3-propanediol enantiomer electrode as the working electrode, platinum electrode as the counter electrode, and saturated calomel electrode as the reference electrode. The three-electrode system was immersed in a prepared 0.1M K3Fe(CN)6 solution at room temperature and a differential pulse test was performed. The potential range was -0.2 to 0.6 V. Figure 5 .

[0054] Comparative Example

[0055] (1) Preparation of CS-SA mixed solution: weigh 25 mg of CS and place it in a 25 ml volumetric flask, add 1% dilute acetic acid solution to dissolve and dilute to the scale; weigh 25 mg of SA and place it in a 25 ml volumetric flask, add deionized water to dissolve and dilute to the scale; mix CS and SA in a ratio of 1:1, ultrasonicate for 1 h, and stir at 60°C for 24 h to prepare a CS-SA mixed solution.

[0056] Take 8 μL of the mixed solution and apply it on the electrode surface, place it under an infrared lamp to dry, and use a three-electrode system, with the CS-SA electrode as the working electrode, the platinum electrode as the counter electrode, and the saturated calomel electrode as the reference electrode. Immerse the three-electrode system in the prepared 0.1M K3Fe(CN)6 solution at room temperature, and perform differential pulse testing and cyclic voltammetry scanning. The potential range is -0.2 to 0.6 V. Figure 7 , 8 , Figure 8 The peak current value is 51.9.

[0057] The above is only a preferred specific implementation of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field within the technical scope disclosed by the present invention, according to the technical solution and its concept of the present invention, shall be covered within the protection scope of the present invention. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A 3D-rGO-Fe3O4-CS-SA composite modified electrode for electrochemical chiral recognition of 2-amino-1-(4-nitrophenyl)-1,3-propanediol enantiomers, characterized by: It includes an electrode and a 3D-rGO-Fe3O4-CS-SA composite modified on the surface of the electrode, which is obtained by dropping a 3D-rGO-Fe3O4-CS-SA suspension on the surface of the electrode and then drying it; The preparation method of the 3D-rGO-Fe3O4-CS-SA suspension comprises the following steps: An appropriate amount of 3D-rGO-Fe3O4 powder was weighed to prepare a dispersion. After activating the carboxylic acid groups of 3D-rGO-Fe3O4 with 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide, the dispersion was dispersed in a mixed solution of CS and SA in a mass ratio of 1:1, and ultrasonicated and stirred to obtain a 3D-rGO-Fe3O4-CS-SA suspension; the ratio of the total mass of CS and SA to the mass of 3D-rGO-Fe3O4 powder was 5:

4.

2. The method for preparing the 3D-rGO-Fe3O4-CS-SA composite modified electrode according to claim 1, characterized in that: The steps include: (1) Preparation of 3D-rGO-Fe3O4 powder: Weigh the designed amount of GO and disperse it in deionized water, and then sonicate it. Add L-cysteine ​​and FeCl3·6H2O to the above solution, then quickly drop ammonia water, heat the mixture, cool it to room temperature, repeat hysteresis separation, wash it with deionized water, and freeze-dry it to obtain 3D-rGO-Fe3O4 powder. (2) Preparation of 3D-rGO-Fe3O4-CS-SA suspension: Weigh an appropriate amount of 3D-rGO-Fe3O4 powder to prepare a dispersion, activate the carboxylic acid groups of 3D-rGO-Fe3O4 with 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide, and then disperse the mixture in a mixed solution of CS and SA in a mass ratio of 1:1, sonicate, and stir to obtain a 3D-rGO-Fe3O4-CS-SA suspension; (3) Preparation of 3D-rGO-Fe3O4-CS-SA modified electrode: Take an appropriate amount of 3D-rGO-Fe3O4-CS-SA suspension and drop it on the electrode surface. Dry it under an infrared lamp to obtain a 3D-rGO-Fe3O4-CS-SA modified electrode.

3. The method for preparing the 3D-rGO-Fe3O4-CS-SA composite modified electrode according to claim 2, characterized in that: In step (1), the mass ratio of GO, L-cysteine, and FeCl3·6H2O is 1:2:

2.

4. The method for preparing the 3D-rGO-Fe3O4-CS-BSA composite modified electrode according to claim 2, characterized in that: The method for preparing the mixed solution of CS and SA includes: dissolving CS in a 1% dilute acetic acid solution to prepare a CS solution; dissolving SA in deionized water to prepare a SA solution, and then uniformly mixing the CS solution and the SA solution.

5. The method for preparing the 3D-rGO-Fe3O4-CS-BSA composite modified electrode according to claim 2, characterized in that: The mass concentration ratio of EDC·HCl to NHS is 1.2:

1.

6. The method for preparing the 3D-rGO-Fe3O4-CS-SA composite modified electrode according to claim 2, characterized in that: The drop coating amount of 3D-rGO-Fe3O4-CS-SA on the electrode surface is 0.0226 mg / cm 2 .

7. The use of the 3D-rGO-Fe3O4-CS-SA composite modified electrode as claimed in claim 1, characterized in that: The method is used for chiral identification of 2-amino-1-(4-nitrophenyl)-1,3-propanediol enantiomers, comprising the following steps: weighing a certain amount of R- / S-2-amino-1-(4-nitrophenyl)-1,3-propanediol and placing it in a volumetric flask, adding a certain amount of prepared phosphate buffer solution PBS, shaking to obtain an enantiomer solution, immersing a 3D-rGO-Fe3O4-CS-SA composite modified electrode in the enantiomer solution, taking it out, placing it under an infrared lamp for drying, and thus obtaining a 2-amino-1-(4-nitrophenyl)-1,3-propanediol enantiomer electrode; A three-electrode system was used, with 2-amino-1-(4-nitrophenyl)-1,3-propanediol enantiomer electrode as the working electrode, platinum electrode as the counter electrode, and saturated calomel electrode as the reference electrode. The three-electrode system was immersed in a prepared 0.1M K3Fe(CN)6 solution at room temperature for differential pulse testing in a potential range of -0.2 to 0.6V.

Citation Information

Patent Citations

  • Chiral recognition to tryptophan enantiomer containing zinc ion by chiral sensor based on chitosan / sodium alginate

    CN105044178A

  • Preparation method and application of 3D-rGO / Fe3O4-AuNPs / HP-beta-CD composite material

    CN110231384A